(untitled) (Al-Qamar, 2021)
The Article describes that Language is an effective tool for communication. In absence of a proper language, it is hard to express oneself. It is language through which one can ask and request other for any purpose of interest. The following article describes Arabic Language, its origination and evolution in Kashmir. Arabic as a language influenced other languages around the Globe. The article describes Arabic influence and impact on Kashmiri, Language and the comparison of Alphabets and Grammars of Kashmiri and Arabic languages. The article also describes arrival of Islam in Kashmir, and sources through which Islam emerged in Kashmir. The Article also discuss about those writers and translators who have translated the Holy Quran in Kashmiri Language.